Entrepreneurship Qualities of Member of Chamber of Commerce and Industries (CCI) of Nepal - Silwal, Yam Bahadur; Manandhar, Kamal Das (Journal of Advanced Academic Research, 2018)
Entrepreneurship is the capacity for innovation and caliber to introduce innovative techniques in the business operations whereas entrepreneurship quality is the professional application of knowledge, skills and competencies. Entrepreneurship qualities include the management skill, leadership skill, communication skill, decision making skill, creative and innovativeness, risk taking skill etc. the qualities come either by experience or by education and training. The study has focused to identify the entrepreneurship qualities of the member of chamber of commerce and Industries (CCI). The study is conducted in the four districts among the 400 respondent. The data was collected by using the structured questionnaire and collected data is analyzed through the statistical model. Factor analysis is done to present the data. The result shows that there are two major entrepreneurship quality factors: psychological and managerial factor. Each factor has three to four sub-qualities/variables. The study found the more importance of creativity & innovativeness, hardworking, good management skill and decision making skill.